2022
DOI: 10.1186/s13102-022-00493-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the Baduanjin exercise on COVID-19-related anxiety, psychological well-being and lower back pain of college students during the pandemic

Abstract: Background This study aimed to examine the effect of Baduanjin exercise on COVID-19-related anxiety, psychological well-being, and the lower back pain of college students during the coronavirus pandemic in China. Setting The study was carried out in a temporary experimental center of four universities in Wenzhou city in Zhejiang Province, China. Population 387 participants who were college students wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 83 publications
1
29
0
Order By: Relevance
“…After the intervention of the cervical and thoracic "Daoyin" training, anxiety scores in UCS college students were found to decrease signi cantly. The ndings are consistent with other studies demonstrating that the bene ts of qigong exercise for reducing anxiety symptoms are substantial [30,31].…”
Section: Discussionsupporting
confidence: 91%
“…After the intervention of the cervical and thoracic "Daoyin" training, anxiety scores in UCS college students were found to decrease signi cantly. The ndings are consistent with other studies demonstrating that the bene ts of qigong exercise for reducing anxiety symptoms are substantial [30,31].…”
Section: Discussionsupporting
confidence: 91%
“…PA can improve the psychological state of healthy people and patients, which is beneficial to the prevention and treatment of various diseases [ 12 ]. Similarly, Li et al, found that the “Baduanjin” exercise alleviated the anxiety related to COVID-19 and improved the psychological well-being of college students [ 34 ]. “Green exercise” refers to physical activity in the presence of nature, which positively impacts mental health.…”
Section: Resultsmentioning
confidence: 99%
“…To reduce excessive screening, which could result in unnecessary barriers to adopting an active lifestyle, preparticipation should only be conducted for individuals at risks, such as individuals with known cardiovascular, metabolic, or renal diseases who are going to engage in competitive sports or vigorous PA. [34][35][36] From 1995 search results, we found seven published studies examining PA interventions in university settings (TABLE 1). Four of them examined exercise intervention [37][38][39][40] and the leftovers examined behavioral intervention. [41][42][43] All studies that examined health outcomes reported PA benefits, including improved cardiorespiratory fitness, body composition, lipid profile, mood, mental health, and sleep quality.…”
Section: Benefits Versus Risks Associated With Pamentioning
confidence: 99%